Architecture Mosque in Indonesia: The Typical Pattern and Its Shifting Form from The Period of The Kingdom to The Emergence of The YAMP Mosque Phenomenon - Doni Sastra (Journal of Architectural Research and Design Studies, 2023)
Mosques in Indonesia play a significant role as public facilities closely intertwined with society and architecture. They are part of Indonesia's long history, continuously evolving with the changing times. This article attempts to examine the changes in mosque development over the years and seeks to understand the evolving forms. The Inquiry in this article begins with the Kingdom era, continues through the colonial period, and the era of independence, and leads to the emergence of the YAMP mosque phenomenon, using literature review and comparative analysis of secondary data as comprehensive writing content. The influence of modernization on mosque architecture in Indonesia has resulted in a variety of archetypes, each carrying different meanings. The archetype of multi-tiered roofs (tajug) and domes resurfaced after its initial appearance, with similar symbolism but employing different materials and technologies. The architecture of mosques during the post-emergence period those archetypes, tend nostalgic and can be closely associated with industrial and universal forms. Keywords: Archetype; morphology:Indonesia; Mosque architecture